A model of caregiver paediatric HIV disclosure decision-making. Issue 3 (2nd April 2016) - Evangeli, Michael; Kagee, Ashraf
Abstract : Many of the over 3 million HIV-positive children will only be told of their status as adolescents. Knowing one's status may increase treatment adherence, reduce onward HIV transmission, increase trust in caregivers and maximise available support. Yet deciding whether, what, how and when to tell HIV-positive children about their condition is challenging for caregivers. We systematically review HIV disclosure theories before presenting a process model of caregiver paediatric HIV disclosure decision-making. The model, consisting of both a pre-intention and a post-intention stage, integrates individual and contextual determinants. It aims to be situationally specific, broadly applicable and consistent with the empirical literature. Research and practice implications are discussed.